Venous Thromboembolism and Major Bleeding in Patients With Coronavirus Disease 2019 (COVID-19): A Nationwide, Population-Based Cohort Study. (5th January 2021) - Dalager-Pedersen, Michael; Lund, Lars Christian; Mariager, Theis; Winther, Rannva; Hellfritzsch, Maja; Larsen, Torben Bjerregaard; Thomsen, Reimar Wernich; Johansen, Nanna Borup; Søgaard, Ole Schmeltz; Nielsen, Stig Lønberg; Omland, Lars Haukali; Lundbo, Lene Fogt; et al.
Abstract: Background: Venous thromboembolism (VTE) is a potentially fatal complication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, and thromboprophylaxis should be balanced against risk of bleeding. This study examined risks of VTE and major bleeding in hospitalized and community-managed SARS-CoV-2 patients compared with control populations. Methods: Using nationwide population-based registries, 30-day risks of VTE and major bleeding in SARS-CoV-2 positive patients were compared with those of SARS-CoV-2 test-negative patients and with an external cohort of influenza patients. Medical records of all COVID-19 patients at 6 departments of infectious diseases in Denmark were reviewed in detail. Results: The overall 30-day risk of VTE was 0.4% (40/9460) among SARS-CoV-2 patients (16% hospitalized), 0.3% (649/226 510) among SARS-CoV-2 negative subjects (12% hospitalized), and 1.0% (158/16 281) among influenza patients (59% hospitalized). VTE risks were higher and comparable in hospitalized SARS-CoV-2 positive (1.5%), SARS-CoV-2 negative (1.8%), and influenza patients (1.5%). Diagnosis of major bleeding was registered in 0.5% (47/9460) of all SARS-CoV-2 positive individuals and in 2.3% of those hospitalized. Medical record review of 582 hospitalized SARS-CoV-2 patients observed VTE in 4% (19/450) and major bleeding in 0.4% (2/450) of ward patients, of whom 31% received thromboprophylaxis. Among intensive care patients (100% received thromboprophylaxis), risks were 7% (9/132) for VTE and 11% (15/132) for major bleeding. Conclusions: Among people with SARS-CoV-2 infection in a population-based setting, VTE risks were low to moderate and were not substantially increased compared with SARS-CoV-2 test-negative and influenza patients. Risk of severe bleeding was low for ward patients, but mirrored VTE risk in the intensive care setting. Abstract : Risks of venous thrombolism and major bleeding were low to moderate in hospitalized and community-managed COVID-19 patients. These risks were comparable with patients suspected of but testing negative for SARS-CoV-2 and with influenza patients.